Assisted Oocyte Activation With Calcium Ionophore Improves Pregnancy Outcomes and Offspring Safety in Infertile Patients: A Systematic Review and Meta-Analysis - Shan, Yinghua; Zhao, Huishan; Zhao, Dongmei; Wang, Jianhua; Cui, Yuanqing; Bao, Hongchu (Frontiers in Physiology, 2022)
This study aimed to evaluate the efficacy and safety of calcium ionophore during assisted oocyte activation (AOA). This meta-analysis contained randomized controlled trials, prospective observational and retrospective trials. Summary odds ratio (OR) with 95% confidence intervals (CIs) was calculated clinical pregnancy rate and live birth rate. Both fixed and random effects models were applied. A total of 22 studies were included into this meta-analysis. Seventeen included studies showed calcium ionophore increased the clinical pregnancy rate (OR, 2.14; 95% CI, 1.38-3.31). Similarly, fourteen studies indicated that AOA with calcium ionophore during ICSI improved the live birth rate considerably (OR, 2.65; 95% CI, 1.53-4.60). Moreover, fertilization, blastocyst formation and implantation rate were higher after using AOA with calcium ionophore combined with ICSI. In addition, calcium ionophore did not increase top-quality embryo rate, cleavage rate, miscarriage rate, congenital birth defects and neonatal sex ratio. Therefore, calcium ionophore followed by ICSI not only significantly improved live birth and overall pregnancy, but also did not affect the incidence of miscarriage, congenital birth defects and neonatal sex ratio. This meta-analysis indicated that using calcium ionophore to activating oocyte was beneficial for couples with poor fertilization rates following ICSI.